Proyecto de creación de una herramienta para niños con autismo leve (2019)
In this research, the topic of autism is investigated in a way general to mild autism specifically in infants in order to identify the ways of learning and understanding that best adapt to your pace of life, this leads to discovering the visual learning style that breaks down a range of visual possibilities to work with the child. As material to be used, it is proposed design an illustrated story to support their visual understanding, to achieve this carries out a prior investigation between illustration and autism, the relationship that is develops between these areas where beneficial results can be obtained for the child by enhancing their visual learning style through storytelling